Da "Meca do Contrabando" ao "Tigre Guarani" - o novo Paraguai nas páginas de Veja: mudança de enfoque ou defesa da hegemonia? - Figueira Sobrinho, Nelson (2019)
This research analyzes the process of change of focus by Veja magazine in the coverage of the news related to Paraguay, especially those that talk about the relation of the country with Brazil, and studies the purpose of this new media representation. The hypothesis is that this new approach is linked to the industrialization of the Guarani country, which comes from the maquila facilities (sub-contractor companies which produce for the export market), whose matrices are mostly Brazilian. Starting on January 10th, 2007, with the publication "The Smuggling Mecca", in the special booklet "Crime", and ending on January 11th, 2017, with the story "The Guarani tiger", the purpose of this research is to investigate if such indications were pertinent and, if so, to identify the interests of the magazine and who the publication represents: whether its readers or a class, whether Brazil or a specific government. At the same time, the study also tries to point out how the weekly magazine’s process of change of focus is developed in relation to the materials that deal with the Guarani country; how textual and graphic resources are used by the publication to report facts related to Paraguay; what the role of the readers is in this process and, finally, if such a change of focus is justified by the supposed industrialization that Paraguay is undergoing. In order to answer these questions, a theoretical framework based on the concepts of Antonio Gramsci on hegemony and on cultural studies, especially the ones from MartínBarbero, is used to analyze questions related to the media phenomenon. The work is subdivided into a presentation of the magazine’s history, followed by a narrative of the path for choosing the method. In the research, it is selected the index method, whose reference is the historian Carlo Ginzburg. Right after that, the analysis of the object of research begins, obeying the temporality and the historical facts, being them political or economical, involving Brazil and Paraguay or the textual and linguistic aspects used by the magazine. At the end, data are presented concerning the maquiladora industries and related to the economic and social areas and it is tried to confront them with the statements of the publication, which attributed, as demonstrated in the course of the research, the growth of the neighboring country to the Brazilians. It’s concluded that Veja magazine acts in defense of the hegemonic interests of Brazil over Paraguay, but serving its convictions as a media, because it takes for itself the voice of its reader, the voice of the class it represents – or believes to represent. It is also observed that the confessedly liberal weekly magazine claims that Brazil should be the natural leader of Latin America because of its size, location, and economy, and that it cannot relinquish its position, in defense of the interests of Brazilians.